KRISIS EKONOMI GLOBAL ERA PANDEMI COVID-19 (STUDI KASUS: MENURUNNYA NILAI TUKAR RUPIAH TERHADAP DOLAR AMERIKA SERIKAT PERIODE FEBRUARI-MARET 2020 - Ela Nuraeni; Ismiyatun Ismiyatun (Universitas Wahid Hasyim Semarang, 2021)
In 2020 the world is threatened with a global economic crisis as a result of the COVID-19 Pandemic. The global economic crisis is being felt by all countries in the world because of the increasing spread of the COVID-19 virus. The COVID-19 pandemic has a huge impact on the Indonesian economy. One of the impacts is the reduction of the rupiah exchange rate against the United States dollar for the February-March 2020 period. This study aims to determine the factor of the decline in the rupiah exchange rate against the United States dollar for the February-March 2020 period. The oni research method is a qualitative descriptive method. In 2020 the world is threatened with a global economic crisis as a result of the COVID-19 Pandemic. The global economic crisis is being felt by all countries in the world because of the increasing spread of the COVID-19 virus. The results of the research on the decline in the rupiah exchange rate against the United States dollar for the February-March 2020 period included external factors of changes in the World and Internal Economic System including the inflation rate, income level, interest rates, the amount of money in circulation, balance of payments. Keyword: COVID-19, Rupiah Exchange Rate, United States Dollar Abstrak Tahun 2020 dunia terancam krisis ekonomi global akibat dari Pandemi COVID-19. Krisis ekonomi global di rasakan oleh seluruh negara di dunia karena semakin merebaknya virus COVID-19. Pandemi COVID-19 sangat berpengaruh terhadap perekonomian Indonesia. Salah satunya dampaknya yaitu menuruunya nilai tukar rupiah terhadap dolar Amerika Serikat Periode Februari-Maret 2020 Penelitian ini bertujuan untuk mengetahui faktor menurunnya nilai tukar rupiah terhadap dolar Amerika Serikat periode Februari-Maret 2020. Metode penelitian ini adalah metode dikriptif kualitatif. Tahun 2020 dunia terancam krisis ekonomi global akibat dari Pandemi COVID-19. Krisis ekonomi global di rasakan oleh seluruh negara di dunia karena semakin merebaknya virus COVID-19. Hasil dari penelitian menurunnya nilai tukar rupiah terhadap dolar Amerika Serikat periode Februari-Maret 2020 adanya faktor Eksternal Perubahan Sistem Perekonomian Dunia dan Internal meliputi laju inflasi,tingkat pendapatan, suku bunga, jumlah uang yang beredar, neraca pembayaran. Kata Kunci: COVID-19, Nilai Tukar Rupiah, Dolar Amerika serikat.